Microtensile Bond Strength of Total-Etch and Self-Etch Universal Adhesives Containing 10-MDP: A Systematic Review - Ismail, I. Hisham; Razak, N.A. Abdul; Ramzi, N.D. Mohd; Yusof, M.Y.P. Mohd (The Journal of Dentists, 2022)
A systematic review was performed to compare the human dentin microtensile bond strength of universal adhesives with 10-MDP when used as total-etch and self-etch strategies. Literature search was done on October 2019 without limitations on the language of publication, in four databases: PubMed, Web of Science, Scopus, and EBSCO. Additional manual search was done for the grey literature articles: OpenGrey and OpenThesis. Studies that evaluated the dentin bond strength of universal adhesives with 10-MDP using total-etch and self-etch strategy from the year 2000 up till October 2019 were included. The initial search resulted in 5121 references: 2234 from PubMed, 1814 from Scopus, 516 from Web of Science, 553 from EBSCO and 4 from OpenThesis. After full text analysis, 30 references were included in this systematic review. Seven different universal adhesives with 10-MDP were evaluated for dentin microtensile bond strength comparing total-etch and self-etch strategies: Single Bond Universal/Scotchbond Universal (3M ESPE), All Bond Universal (Bisco), Clearfil Universal Bond (Kuraray), G-Premio Bond (GC Corp), Tetric Bond Universal (Ivoclar Vivadent), Ambar Universal (FGM) and One Coat 7 Universal (Coltene). The total-etch strategy improved the dentine microtensile bond strength compared to self-etch strategy for all universal adhesives when stored in all three conditions: 24h, thermocycling and long-term immersion according to ISO (TS 11405:2015(E)). The evidence suggests that microtensile bond strength of universal adhesives containing 10-MDP may be improved utilizing total-etch strategy compared to self-etch strategy. This study provides valuable information on the importance of appropriate dentin adhesives strategy that affect success rate of restorations, which helps clinicians to make informed decisions on the strategy to be used during restorations in practice.